Latest Advances in Nanoplasmonics and Use of New Tools for Plasmonic Characterization - Barbillon, Grégory (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Nanoplasmonics is an area that uses light to couple electrons in metals, and can break the diffraction limit for light confinement into subwavelength zones, allowing for strong field enhancements. In the last two decades, there has been a resurgence of this research topic and its applications. Thus, this Special Issue presents a collection of articles and reviews by international researchers and is devoted to the recent advances in and insights into this research topic, including plasmonic devices, plasmonic biosensing, plasmonic photocatalysis, plasmonic photovoltaics, surface-enhanced Raman scattering, and surface plasmon resonance spectroscopy.